1989
DOI: 10.1128/mcb.9.5.1940
|View full text |Cite
|
Sign up to set email alerts
|

Primase p49 mRNA expression is serum stimulated but does not vary with the cell cycle.

Abstract: Expression of the small-subunit p49 mRNA of primase, the enzyme that synthesizes oligoribonucleotides for initiation of DNA replication, was examined in mouse cells stimulated to proliferate by serum and in growing cells. The level of p49 mRNA increased -10-fold after serum stimulation and preceded synthesis of DNA and histone H3 mRNA by several hours. Expression of p49 mRNA was not sensitive to inhibition by low concentrations of cycloheximide, which suggested that the increase in mRNA occurred before the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1990
1990
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…In actively cycling cells, however, the transcript, protein, and enzymatic activity of human DNA polymerase a are constitutively expressed throughout the cell cycle. Similar findings have been observed in several mammalian replication proteins (Sherley and Kelly, 1988;Wahl et al, 1988;Morris and Mathews, 1989;Tseng et al, 1989). It was also shown that in actively cycling cells the human DNA polymerase a protein is phosphorylated in a cell cycledependent manner .…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…In actively cycling cells, however, the transcript, protein, and enzymatic activity of human DNA polymerase a are constitutively expressed throughout the cell cycle. Similar findings have been observed in several mammalian replication proteins (Sherley and Kelly, 1988;Wahl et al, 1988;Morris and Mathews, 1989;Tseng et al, 1989). It was also shown that in actively cycling cells the human DNA polymerase a protein is phosphorylated in a cell cycledependent manner .…”
Section: Introductionsupporting
confidence: 76%
“…In mammalian cells, most genes involved in DNA synthesis or metabolism are expressed constitutively during the cell cycle. In some cases, the proteins are modified posttranslationally in a cell cycle-dependent manner (Sherley and Kelly, 1988;Wahl et al, 1988;Morris and Mathews, 1989;Tseng et al, 1989;Nasheuer et al, 1991). In S. cerevisiae, the transcriptional expression of many DNA synthesis genes are coordinately induced at the Gl/S boundary.…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA levels of the PCNA gene are growth regulated (1,15), as are those of other genes coding for proteins of the DNA-synthesizing machinery, such as the genes for TK (6,15,20,37), DNA polymerase alpha (41), RNA primase (40), and thymidylate synthase (16). In continuously dividing cells such as HeLa cells, the mRNA levels of some of these genes (those encoding TK [33], DNA polymerase alpha [41], RNA primase [40], and PCNA [23]) vary little throughout the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In continuously dividing cells such as HeLa cells, the mRNA levels of some of these genes (those encoding TK [33], DNA polymerase alpha [41], RNA primase [40], and PCNA [23]) vary little throughout the cell cycle. However, in quiescent fibroblasts or fibroblastlike cells in culture, the mRNA levels of these genes are very low or undetectable and increase sharply when serum-stimulated cells reach the G1/S boundary.…”
Section: Discussionmentioning
confidence: 99%
“…In experiments where exponentially growing cells were separated by counterflow centrifugation it has become clear that both mRNA species are constitutively expressed throughout the cell cycle (Parmacek et al, 1989;Barker and Newburger, 1990). Thus, as described for several other growth-induced genes (Thompson et al, 1985;Wahl et a]., 1988;Tseng et al, 1989), expression of the 4F2 antigen and transferrin receptor increases upon activation of quiescent cells, but subsequently remains constant in continuously cycling cells. This rules out a regulatory control that is specific to the GI phase in each cycle.…”
Section: Discussionmentioning
confidence: 71%